1 - L’Afrique ne va-t-elle pas vers une diminution de ses avantages comparatifs? 10.4314/ad.v25i3.22101 - Ebe, Bruno Bekolo (Africa Development, 2000)
The fall of Berlin Wall had put an end to the world bi-polarisation: communist and capitalist systems. Nowadays, there is a multitude of poles that are transforming the international trade. The mastering by the industrialised countries and the New Industrialised Countries (NIC) of technology, research-development, and innovation places Africa far behind in this international trade, and causes the loss of its comparative advantages. In this article, the author reminds us of the origins of those comparative advantages that mainly come from agriculture and forestry and primary products. Then he examines the explanatory factors of this loss: the shift in the production systems, in world supply and demand factors; the conditions of competition in world markets, and internal elements distinctive of the evolution peculiar to African economies. At last, he suggests some ways of recovering this loss of comparative advantages.